Microsurgical Localization of the Cochlea in the Extended Middle Fossa Approach - Forbes, Jonathan A.; Rivas, Alejandro; Tsai, Betty; Ehtesham, Moneeb; Zuckerman, Scott; Wanna, George; Weaver, Kyle (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objective In the extended middle fossa approach, a portion of the petrous bone known as Kawase's rhomboid can be drilled to expose the posterior fossa through a middle fossa corridor. During this bony resection, the cochlea is placed at risk. The objective of this study was to objectively detail the position of the cochlea in relation to reliable surgical landmarks.Methods Eleven cadaveric specimens were dissected—including six cadaveric heads and five dry temporal bones by means of an anterior petrosectomy with skeletonization of the cochlea. Three anatomic measurements describing the location of the cochlea in relation to the extrapolated intersection of the greater superficial petrosal nerve (GSPN) and facial nerve were recorded. These measurements were then correlated with thin-cut temporal bone computed tomography scans from 25 patients with morphologically normal inner ears.Results In the cadaveric specimens, the anterior border of the membranous basal turn of the cochlea was located an average of 7.56 mm (6.4 to 8.9 mm) anterior to the extrapolated junction of the GSPN and facial nerve, as measured along the course of the GSPN. The medial border of the membranous cochlea (medial margin of basal turn) was located an average of 8.2 mm (6.9 to 8.9 mm) medial to the extrapolated junction of the GSPN and facial nerve, as measured along the course of the facial nerve. The average maximum distance from the extrapolated junction of the GSPN and facial nerve to the membranous cochlea was 9.3 mm (8.2 to 10.3 mm). These anatomic measurements correlated well with radiologic measurements of the same parameters.Conclusion When drilling Kawase's rhomboid, it is useful to locate the extrapolated junction of the GSPN and the facial nerve. Drilling of the anteromedial petrous bone outside of a radius of 12.5 mm from the extrapolated junction of GSPN and facial nerve appears to be associated with a low degree of risk to the cochlear apparatus.
Keywords: middle fossa approach; Kawase's rhomboid; cochlea; greater superficial petrosal nerve